2008
DOI: 10.1038/sj.bjc.6604303
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of tobacco smoking on cancer and cardiovascular disease in urban black South Africans

Abstract: Demographic and lifestyle information from 9690 black patients diagnosed with cancer or cardiovascular disease was collected in an ongoing case -control study in Johannesburg, South Africa. Compared to never smokers, the odds ratio (OR) for lung cancer among current smokers was 16.3 (95% confidence interval (CI), 9.6 -27.6) for men and 6.4 (95% CI, 4.0 -10.4) for women. The corresponding OR for other smoking-related cancers was 4.6 (95% CI, 3.7 -5.7) among men and 1.9 (95% CI, 1.6 -2.2) among women, and for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 24 publications
3
42
1
Order By: Relevance
“…Important factors allowed for were age (20 studies), sex (14 studies), skin type/pigmentation/tendency to burn (5 studies), and exposure to sun/sunburn (6 studies); additionally, the population in one study 27 was based on comparisons between twins. Six of the 25 included studies did not provide data in a suitable format 9,14,21,24,29,32 and thus could not be included in the meta-analyses; however, data for these studies are reported narratively.…”
Section: Resultsmentioning
confidence: 99%
“…Important factors allowed for were age (20 studies), sex (14 studies), skin type/pigmentation/tendency to burn (5 studies), and exposure to sun/sunburn (6 studies); additionally, the population in one study 27 was based on comparisons between twins. Six of the 25 included studies did not provide data in a suitable format 9,14,21,24,29,32 and thus could not be included in the meta-analyses; however, data for these studies are reported narratively.…”
Section: Resultsmentioning
confidence: 99%
“…The low frequency of oral leukoplakia in black persons may be attributed to the fact that in general, black persons seek medical treatment late in the course of their disease, and by the time of diagnosis, the oral leukoplakia has already undergone malignant transformation and progressed to oral squamous cell carcinoma (9,50); and to the fact that in South Africa, black persons smoke tobacco less than do white persons (10,11). Indeed, in this study, 62% of black patients with oral leukoplakia smoked tobacco compared to 82% of white patients with oral leukoplakia (Table VII).…”
Section: Discussionmentioning
confidence: 99%
“…This apparent low prevalence of oral leukoplakia in black South Africans is difficult to explain. This may be due to the fact that in the pre-1994 era, black people had limited access to government health facilities, that black persons in South Africa smoke less compared to other South African population groups, and that in general, black people seek medical treatment late in the course of their disease and by the time of diagnosis, the oral leukoplakia has already transformed into oral SCC (10,11). It is however possible that for reasons unknown, the prevalence of oral leukoplakia in South African blacks is inherently low.…”
Section: Introductionmentioning
confidence: 99%
“…According to their observations, education level was inversely associated with the mortality rate of all types of cancer, and the difference was most pronounced in individuals with up to 12 years of education, and in those with more than 12 years of education. 29 In a South African study, Stein et al 11 reported that 68% of black patients with lung cancer had completed a maximum of five years of schooling. According to the United Nations Educational, Scientific and Cultural Organization, in 2011, the mean number of years of school attendance by adults older than 25 years of age in South Africa was 8.5 years, 31 implying that a substantial proportion of the total South African population has an education level of lower than Grade 9.…”
Section: 29mentioning
confidence: 99%